Modular shape-changing tensegrity-blocks enable self-assembling robotic structures - Zhao, Luyang; Jiang, Yitao; Chen, Muhao; Bekris, Kostas; Balkcom, Devin (Nature communications, 2025)
Modular robots are currently designed to perform a variety of tasks, primarily focusing on locomotion or manipulation through the reconfiguration of rigid modules. However, the potential to integrate multiple functions, such as making each robot deployable and capable of building lattice structures for self-construction and infrastructure creation, remains largely unexplored. To advance the field, we hypothesize that combining tensegrity principles with modular robotics can create lightweight, deformable units capable of integrating three critical functions within a single design: navigating varied terrains, manipulating arbitrary shape objects, and assembling weight-sustainable, active large infrastructures. Here, we designed untethered modular robots that are deformable, lightweight, deployable, outdoor-scale, capable of bearing loads, and capable of 3D attachment and detachment. With these characteristics, the system can form various 3D structures using different assembly methods, such as walking into position or being transported by rotorcraft. The deformability and lightweight nature of each block enable the assembled structures to dynamically change shape, providing capabilities such as added compliance during locomotion and manipulation and the ability to interact with the environment in tasks like tent and bridge assemblies. In summary, we suggest that integrating lightweight and deformable properties into modular robot design offers potential improvements in their adaptability and multi-functionality. Creating modular robots that can adapt to various tasks and construct temporary structures remains a challenge. The authors designed and tested lightweight, deformable, untethered robots capable of effective locomotion, versatile manipulation, and rotorcraft-assisted 3D assembly.